2016
DOI: 10.1007/s00436-016-4943-3
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and tick-borne pathogens in wild birds in Greece

Abstract: Wild birds are common hosts of ticks and can transport them for long distances, contributing to the spreading of tick-borne pathogens. The information about ticks on birds and tick-borne pathogens in Greece is limited. The present study aimed to evaluate the prevalence and species of ticks infesting wild resident birds (mostly small passerines) in Greece, and to assess Borrelia and Rickettsia infection in the collected ticks. Detection of Borrelia burgdorferi s.l. was performed by nested PCR targeting the flaB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
3
27
1
Order By: Relevance
“…This is also what we observed on the ancestry recombination graph reconstructed using sequences of the 85 European STs and generated in beasT2 (Bouckaert et al, 2019;Figure 5 Ixodes ricinus is a generalist tick and birds are known to be important hosts for its immature stages (Norte et al, 2012;Santos-Silva et al, 2011). The other tick species (I. frontalis, I. arboricola and I. ventalloi) and genera (Haemaphysalis and Hyalomma) collected from birds in this study have also been previously reported on birds (Diakou et al, 2016;Norte et al, 2012;Pérez-Eid, 2007) and differ in vector competence for Borrelia (Eisen & Lane, 2002;. Some bird species such as hole-nesting birds (P. major and F. albicollis), Poupon et al, 2006), Spain (9.2%; Palomar et al, 2016) and Portugal (7.3%; Norte et al, 2015).…”
Section: Multilocus Sequence Typing/multilocus Sequence Analysis (Msupporting
confidence: 85%
See 1 more Smart Citation
“…This is also what we observed on the ancestry recombination graph reconstructed using sequences of the 85 European STs and generated in beasT2 (Bouckaert et al, 2019;Figure 5 Ixodes ricinus is a generalist tick and birds are known to be important hosts for its immature stages (Norte et al, 2012;Santos-Silva et al, 2011). The other tick species (I. frontalis, I. arboricola and I. ventalloi) and genera (Haemaphysalis and Hyalomma) collected from birds in this study have also been previously reported on birds (Diakou et al, 2016;Norte et al, 2012;Pérez-Eid, 2007) and differ in vector competence for Borrelia (Eisen & Lane, 2002;. Some bird species such as hole-nesting birds (P. major and F. albicollis), Poupon et al, 2006), Spain (9.2%; Palomar et al, 2016) and Portugal (7.3%; Norte et al, 2015).…”
Section: Multilocus Sequence Typing/multilocus Sequence Analysis (Msupporting
confidence: 85%
“…Ixodes ricinus is a generalist tick and birds are known to be important hosts for its immature stages (Norte et al, ; Santos‐Silva et al, ). The other tick species ( I. frontalis , I. arboricola and I. ventalloi ) and genera ( Haemaphysalis and Hyalomma ) collected from birds in this study have also been previously reported on birds (Diakou et al, ; Norte et al, ; Pérez‐Eid, ) and differ in vector competence for Borrelia (Eisen & Lane, ; Heylen, Krawczyk, et al, ; Heylen, Sprong, et al, ). Some bird species such as hole‐nesting birds ( P. major and F. albicollis ), T. merula and T. philomelos were hosts for different tick species; however, the opportunities for cofeeding transmission of B. burgdorferi s.l.…”
Section: Discussionsupporting
confidence: 73%
“…were found on birds during migration (Hornok et al 2014a, b). In the Danube Delta I. ricinus was dominant, however I. arboricola, I. redikorzevi and H. punctata also occurred (Sándor et al 2014), in Greece I. frontalis, I. acuminatus, H. aegyptium and H. marginatum were recorded (Diakou et al 2016). In Egypt and Cyprus detailed research by Nuorteva and Hoogstraal (1963), Hoogstraal et al (1963Hoogstraal et al ( , 1964, Kaiser et al (1974) indicated that birds are able to transport at least 13 ticks species H. rufipes, A.…”
Section: Discussionmentioning
confidence: 97%
“…Different sections of the GI tract are labeled above the graphs and include: crop (CR), ceca (CE), cloaca (CL) and feces (F). birds (Keller et al 2011, Wallménius et al 2014, Diakou et al 2016.…”
Section: Proteobacteriamentioning
confidence: 99%